PERANCANGAN USER INTERFACE APLIKASI MOBILE EXPLORE PARIWISATA KABUPATEN KEBUMEN - Miftahul Huda Huda; Farhan Hidayat; Khilda Hania Rohmah; Radityo Priyambudi (LP3M Universitas Putra Bangsa, 2023)
The tourism sector is an important sector and plays a strategic role in a district, promotion and marketing techniques are the most important part for the development of a tourism place. Mobile applications provide solutions in conducting promotion and marketing in the tourism sector. This journal aims to design an effective user interface (UI) for tourism applications in Kebumen Regency. The purpose of this study is to design an efficient user interface design for tourism mobile applications, taking into account user convenience and satisfaction. The method used in this design includes data collection through analysis and interviews. So that from the initial data collection which includes destination information and tourist recommendations. Furthermore, the design of this User Interface will be developed using the prototype method.